Clustering Technique in Teaching Writing Descriptive Text - Wiki Tedi Rahmawati (English Teaching and Linguistics Journal (ETLiJ), 2021)
This research aimed to find out the significant effect of clustering technique on the eighth grade students’ achievement in writing descriptive text. The research was conducted at a private school in Tanjung Morawa, Medan. It was conducted by applying experimental research design and the sample consisted of 60 students which were divided into two groups. They were experimental group which were taught by applying the clustering technique and control group which were taught without any specific technique. Each group consisted of 30 students. The instrument used to collect the data was writing test of descriptive text. The data obtained were analyzed using t-test. The test found out that the scores of the students in the experimental group were significantly higher than the scores of the students in the control group (t-observed value 2.11 > t-table value 2.004). It was concluded that clustering technique had a significant effect on students’ achievement in writing descriptive text.